Analisis Ketertarikan Siswa Sekolah Dasar terhadap Kebudayaan Indonesia - Dwi Wulandari; Vioreza Dwi Yunianti; Yona Wahyuningsih (Departement of Mathematics Education, 2023)
As we know that in fact many elementary school students have less interest in the culture in Indonesia. This makes when students have less interest in culture in Indonesia also decreases the enthusiasm of students when learning about the culture learned in school. The emergence of the problem of declining interest of elementary school students in Indonesian culture is due to the use of gadgets or technology that is only used to play games with a long time of use without being able to use existing technology to find out and learn about their culture. So, looking at these problems, the purpose of this study is to analyze the interest of elementary school students to Indonesian culture. In this study, the authors use a qualitative approach. The results of this study are a variety of approaches to elementary school student to increase their interest in the culture of Indonesia.